Does Parallel Projection is Suitable in Electrical Capacitance Tomography? –A Comparison with Common Approach - Muhammad Faris Aiman Hisham; Yasmin Abdul Wahab; Zainah Md Zain; Mohd Hafiz Fazalul Rahiman; Leow Pei Ling; Rashidah Arsat; Ruzairi Abdul Rahim; Nurhafizah Abu Talip@Yusof; Rohana Abdul Karim; Nor Farizan Zakaria; Nurul Wahidah Arshad; Suzanna Ridzuan Aw; et al. (MyCT Publishers, 2024)
Non-Indexed Publication